Analisis Putusan Panitia Khusus DPRD dalam Mewujudkan Pemerintahan Daerah yang Good Governace: Analysis of the Decision of the DPRD Special Committee in Realizing Good Governance in Regional Government - Ahmad Dhafir; Wahyu Prawesthi; Subekti Subekti; Nur Handayati (UIN Kiai Haji Ahmad Sidiq Jember, 2026)
This study aims to analyze the legal status of the decisions of the Regional House of Representatives’ Special Committee (Pansus DPRD) in regional governance, as well as their legal implications for the obligation of regional governments to follow up on legislative oversight outcomes. This research employs a normative juridical method with statutory and conceptual approaches. The results indicate that the decisions of the Pansus DPRD do not possess legally binding executorial force but are instead recommendatory and persuasive in nature, as stipulated in Law Number 23 of 2014 on Regional Government. Nevertheless, these decisions play a strategic role in the checks and balances mechanism through political and moral influence, and they have the potential to be transformed into regional policies. The legal implications of Pansus decisions are reflected in the strengthening of the principles of accountability, transparency, and proportionality in regional governance. However, the weak follow-up by the executive has led to the suboptimal functioning of legislative oversight. Therefore, it is necessary to strengthen internal DPRD regulations, enhance the obligation of regional governments to respond, and foster synergy with internal government supervisory bodies in order to achieve good regional governance. Abstract Penelitian ini bertujuan untuk menganalisis kedudukan hukum putusan Panitia Khusus (Pansus) DPRD dalam tata kelola pemerintahan daerah serta implikasi hukumnya terhadap kewajiban pemerintah daerah dalam menindaklanjuti hasil pengawasan legislatif. Metode yang digunakan adalah yuridis normatif dengan pendekatan perundang-undangan dan konseptual. Hasil penelitian menunjukkan bahwa putusan Pansus DPRD tidak memiliki kekuatan hukum yang mengikat secara eksekutorial, melainkan bersifat rekomendatif dan persuasif sebagaimana diatur dalam Undang-Undang Nomor 23 Tahun 2014 tentang Pemerintahan Daerah. Meskipun demikian, putusan Pansus memiliki peran strategis dalam mekanisme checks and balances melalui pengaruh politik dan moral, serta berpotensi ditransformasikan ke dalam kebijakan daerah. Implikasi hukum dari putusan Pansus terlihat pada penguatan prinsip akuntabilitas, transparansi, dan proporsionalitas dalam penyelenggaraan pemerintahan daerah. Namun, lemahnya tindak lanjut oleh pihak eksekutif menyebabkan fungsi pengawasan belum berjalan optimal. Oleh karena itu, diperlukan penguatan regulasi internal DPRD, peningkatan kewajiban respons pemerintah daerah, serta sinergi dengan aparat pengawasan internal pemerintah guna mewujudkan tata kelola pemerintahan daerah yang baik.